2022
DOI: 10.3390/ijerph191912197
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Single and Multiple Injuries Due to Static Balance and Movement Quality in Physically Active Women

Abstract: Background: Static balance is a reliable indicator of the musculoskeletal and nervous systems, which is a basis for movement stabilization development. The disorders in this area may increase injury risk (IR). This study investigated the musculoskeletal injury risk due to static balance and movement quality regarding single and multiple injury occurrences in physically active women. Methods: The study sample was 88 women aged 21.48 ± 1.56. The injury data were obtained with a questionnaire, and Deep Squat (DS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Additionally, a systematic review of the incidence of foot injuries among longdistance runners found that the majority of injuries involved the knee (7.2-50%), lower leg (9-32.2%), foot (5.7-39.3%), or thighs (3.4-38.1%) [7]. Furthermore, there are several risks of injury to athletes, including poor flexibility, lack of neuromuscular coordination and muscle imbalance [8]. An athlete's muscle strength imbalance is one of the risk factors for injury [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a systematic review of the incidence of foot injuries among longdistance runners found that the majority of injuries involved the knee (7.2-50%), lower leg (9-32.2%), foot (5.7-39.3%), or thighs (3.4-38.1%) [7]. Furthermore, there are several risks of injury to athletes, including poor flexibility, lack of neuromuscular coordination and muscle imbalance [8]. An athlete's muscle strength imbalance is one of the risk factors for injury [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are several risks of injury to athletes, including poor flexibility, lack of neuromuscular coordination and muscle imbalance [8]. An athlete's muscle strength imbalance is one of the risk factors for injury [8]. Strong parts will compensate for weak parts, which is often the cause of overuse or chronic injuries [9].…”
Section: Introductionmentioning
confidence: 99%